Analysis of 30 Minute Joging and Walking Exercises Results on Body Components - Firdaus, Mochammad Eka Rizqi; Herdyawan, Cikal Triadi; Setyaningrum, Nindy; Ningrum, Erieke Dwi Lutfia; Adilah, Zulfa Marsha; Leksono, Mario Felix Adi Joko; Kurniawan, Endra Ferdy; Pramono, Bayu Agung (Universitas Negeri Surabaya, 2024)
Purpose: This study aims to determine the effectiveness of reducing weight, BMI as well as fat with enjoyable exercise through treatment and control exercises. Materials and Methods: This research utilizes a quantitative approach method. This research was conducted at Surabaya State University on March 15 2024 - April 5 2024. 20 students with an average age of 18 - 20 years participated in this research, they were divided into 2 groups, namely 10 students in the circuit training treatment group and 10 students in the circuit training treatment group. 30 minute walking treatment. Training is carried out within 3 weeks carried out 5 times a week. They do physical activities in the form of jogging and walking. Body composition was carried out using the Tanita scale measuring instrument version BC-545N. The urgency of this research was carried out because there are many teenagers who are obese in Indonesia. Result: The results of this research were that treatment, carried out 5 times a week, and carried out for 3 weeks, was successful in reducing BMI, FAT, MUSCLE, BMR, METABOLIC AGE, dan VISCERAL FAT Conclusion: In conclusion, control training for 30 minutes has an influence on reducing Water, FAT, Muscle, dan Visceral fat